P-051 TAPP IN A COMMUNITY HOSPITAL SETTING : AN EXPERIENCE OF OVER 1000 CASES. (13th October 2022) - Agresta, F; Licitra, E; Mazzarolo, G; Savino, G; Pontarolo, N; Montori, G
Abstract: Aim: We want to share and discuss what we have learned from our 20-year experience in TAPP procedures Material and Methods: We use only all 5 mm trocars, instruments, and 30-degree optics and we always use low intraabdominal pressure (10mmHg). The major technical trick is to carefully prepare the peritoneum flap all around, like a cone, just in order to let the mesh perfectly lie down on the inguinal area. Results: Our TAPP experience is almost more than 1000 cases, elective as an emergency. We use a 10×15 cm LW macroporous monofilament polypropylene mesh. Besides the well known needed physical characteristics of the mesh, on the surgeon's side, a mesh should be smooth, stiff, wide enough to cover all the possible defects, easy to handle, and, especially for its possible use in laparoscopy, with a certain degree of and thickness just what it is needed in order to let it pass through a 5 mm trocar once rolled up. We do not use to fix the mesh anymore because we do believe in the mesh pushed versus the abdominal wall by the intra-abdominal pressure, and in the exact size of the (10×15 cm). Only in case of huge direct hernia we do "lift" without tension the transversalis fascia. Conclusions: Most of the advantages of laparoscopy rely on the minimal access and therefore the benefits of this technique will be greater as the access becomes smaller, together with a no fixed LW mesh.